The Influence of Service Quality and Product Quality on The Royal Pita Maha Company Performance - Dewa Ayu Sri Arimas Dewi; Ni Ketut Purnawati (Green Publisher Indonesia, 2024)
Background: Company performance is a result of operational activities in using the company's resources. The successful contribution of employees will have an impact on the level of customer satisfaction, where satisfied customers will minimize the level of complaints and retention levels and play a role in assessing company performance as evaluation material for company management. Purpose: The purpose of this research is to determine the influence of service quality and product quality on company performance at The Royal Pita Maha. Method: This research is a type of associative research with a quantitative approach. The data collection method was carried out by direct observation, interviews and distributing questionnaires to 160 respondents, namely employees of The Royal Pita Maha who were selected using a non-probability sampling method with a quota sampling technique. The research instrument was tested using validity and reliability tests, then data analysis was carried out using multiple linear regression using SPSS. Results: The research results show that service quality has a positive and significant effect on company performance, as well as product quality has a positive and significant effect on company performance. Conclusion Based on the research results, it is hoped that company management can pay more attention to the company's operational activities through employee contributions in providing services so as to create a sense of security and comfort for customers and pay attention to the ingredients of the products provided so that they remain safe and last a long time so that the company's performance assessment can be even better.